Mini-review: pheochromocytomas causing the ectopic ACTH syndrome. - Ballav, C; Naziat, A; Mihai, R; Karavitaki, N; Ansorge, O; Grossman, AB (2012)
Cushing's syndrome (CS) is a condition associated with high cortisol levels and affects around 0.7-2.4 cases per million population per year [1-3]. Approximately 80 % of cases of CS are secondary to excess adrenocorticotrophin (ACTH) secretion, while in around 20 % the primary abnormality lies in the adrenal, most often an adrenal adenoma or carcinoma. Of the ACTH-dependent causes, some 80-90 % are due to a pituitary adenoma-Cushing's disease-but in a significant proportion the cause is ectopic secretion from a non-pituitary source, the ectopic ACTH syndrome (EAS) [4]. The commonest source of ACTH secretion in these patients is a bronchial carcinoid. However, many other tumors are capable of secreting ACTH, and in most series a small but significant number are secondary to an ACTH-secreting pheochromocytoma. Amalgamating the data from 6 large series of patients with ectopic ACTH, pheochromocytoma was the source of ACTH secretion in 19 out of 363 patients (5.2 %) [5-11]. In this mini-review, we present a patient presenting to our department with a pheochromocytoma as well as Cushing's syndrome due to ectopic ACTH secretion by the pheochromocytoma, and we discuss published cases in the world literature to assess its significance. We emphasize the problems in the simultaneous management of these two serious endocrine conditions.